Information System Security Analysis in the Internet of Things (IoT) Era - Nurrisma (Journal Informatic, Education and Management (JIEM), 2023)
The presence of the Internet of Things (IoT) has provided a new foundation in the development of information systems, but has also raised new challenges related to information security. This research aims to analyze the level of information system security in the context of the IoT era. The research methods used include an in-depth literature survey and critical analysis of security frameworks relevant to IoT. The research results show that while IoT offers great potential to increase efficiency and convenience, it also opens up new avenues for complex and serious security attacks. Security threats related to IoT include network attacks, data theft, and unauthorized access. To overcome this challenge, a holistic and layered approach is needed in securing information systems connected via IoT. The importance of implementing strong security protocols, data encryption, and continuous monitoring of IoT networks cannot be overstated. In conclusion, the success of widespread IoT implementation will be largely determined by efforts to strengthen the security of the information systems involved.